Sodium Alginate: A Green Biopolymer Resource-Based Antimicrobial Edible Coating to Enhance Fruit Shelf-Life: A Review - Anshika Sharma; Arun K. Singh (Colloids and Interfaces, 2025)
Fruits are a significant source of natural nutrition for human health. However, the perishable nature and short shelf life of fruits lead to spoilage, nutrition safety challenges, and other substantial postharvest losses. Edible coatings have emerged as a novel approach in order to enhance the shelf life of perishable fruits by forming a protective barrier against adverse environmental conditions and microbial infections. Sodium alginate is recognized as an excellent polysaccharide (derived from algae, seaweed, etc.) in the food industry for edible fruit coatings because of its non-allergic, biodegradable, non-toxic (safe for human health), inexpensive, and efficient gel/film-forming properties. However, the hydrophilicity of the polysaccharides is a significant concern to prevent the growth of mold and yeast. In recent years, various plant extracts (containing multiple bioactive compounds, including polyphenolic acids) and nanoparticles have been applied in sodium alginate-based edible films and fruit coatings to enhance antimicrobial activity. This review study summarized recent advancements in fabricating plant extracts incorporating sodium alginate-based films and coatings to enhance fruit shelf life. In addition, approaches to preparing edible films and the basic mechanism behind the role of coating materials in enhancing fruit shelf life are discussed. Moreover, the limitations associated with sodium alginate-based fruit coatings and films have been highlighted.